Photoselective vaporization of the prostate in men taking clopidogrel - Spernat, Daniel M. G. (Medknow Publications, 2011)
AIM: To evaluate the peri-operative morbidity of men taking clopidogrel who underwent photoselective vaporisation of the prostate (PVP). PATIENTS AND METHODS: A prospective database was collected. Between March 2005 and July 2010, 480 men underwent PVP. Of these, 18 men underwent PVP treatment while on clopidogrel. The surgery was carried out with either an 80W KTP laser or a 120W lithium triborate laser. RESULTS: In the peri-operative period there were no complications related to PVP. There were no urinary tract infections, nor did any patient require bladder re-catheterisation. No cardiovascular events were reported within 3 months of the procedure. At 3 months post operatively, the International Prostate Symptom Score±standard deviation had improved from was 17.5±10.6 to 9.2±6.1 P<0.05. While the Quality of Life±standard deviation improved from 4.7±1.2 to 2.2±1.5 P<0.01. The maximum flow rate (Qmax), and post void residual volume (PVR) improved from 6.2±3.0 mL/s to 19.7±9.1 mL/s (P<0.01), and 140±102 mL to 59±77 mL (P<0.05), respectively. CONCLUSIONS: PVP is a safe and efficacious in the treatment of high risk patients with bladder outlet obstruction. Further, the ability to continue therapeutic anticoagulation and anti-platelet agents, is a significant advantage over Holmium enucleation of the prostate and conventional transurethral resection of the prostate. Larger studies with greater numbers of patients are required prior to PVP becoming the gold standard for high-risk patients with bladder outlet obstruction.